2009
DOI: 10.1096/fj.09-129585
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time imaging reveals defects of fast axonal transport induced by disorganization of intermediate filaments

Abstract: Intermediate filament (IF) abnormalities frequently appear in neurodegenerative disorders, but how they may contribute to neuronal dysfunction remains unclear. Here, we examined the effects of IF disorganization on the fast axonal transport using time-lapse microscopy. We studied the axonal transport of mitochondria and lysosomes in cultured primary dorsal root ganglion (DRG) neurons derived from mice deficient for neurofilament light (NFL(-/-)), mice overexpressing peripherin (Per), and mice double transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 53 publications
(65 reference statements)
5
45
0
1
Order By: Relevance
“…Similar observations have been made by Broadwell and Cataldo [35] in pituitary axons of the human brain, and in hippocampal pyramidal cells [36] Ctr. 24 and in dorsal root ganglia [37]. Recent data of Hernandez et al [38] showed that induction of neuronal autophagy by using Rapamycin acutely increased AV-formation in presynaptic terminals, decreased the amount of synaptic vesicles and depressed evoked neurotransmitter release.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been made by Broadwell and Cataldo [35] in pituitary axons of the human brain, and in hippocampal pyramidal cells [36] Ctr. 24 and in dorsal root ganglia [37]. Recent data of Hernandez et al [38] showed that induction of neuronal autophagy by using Rapamycin acutely increased AV-formation in presynaptic terminals, decreased the amount of synaptic vesicles and depressed evoked neurotransmitter release.…”
Section: Discussionmentioning
confidence: 99%
“…IFs also impact subcellular organelles other than mitochondria. For example, the positioning, sorting or movement of lysosomes or the crosstalk between lysosomes and endosomes is impacted by vimentin [114] desmin [71], and NF [119]; and vimentin and keratins are important for the transport of melanosomes [120, 121]. Furthermore, nuclear lamin A mutations cause a variety of organelle phenotypes, such as enlarged rough endoplasmic reticulum and mitochondria in mice, and gap junctional protein mislocalization in myocytes [122].…”
Section: Involvement Of Ifs In Specific Stress Contextsmentioning
confidence: 99%
“…Evidence is also emerging that the cytoskeleton, and especially the NF scaffold, acts as a docking platform to organize the topography of organelles within different neuronal compartments. Rearrangements of this topography are dynamically coordinated at least in part by cellular signals regulating the phosphorylation state of the binding partners [137, 143, 163, 193]. Such evidence suggests a range of possibilities for understanding the newly recognized roles of individual NF subunits in modulating synaptic function.…”
Section: Introductionmentioning
confidence: 99%